Predisposing factors and clinical profile of acute severe asthma - Sreenivas, S K; Murthy, K Anjana; Renuka, T (Indian Journal of Child Health, 2017)
Background: Asthma is a chronic inflammatory condition of the lung airways resulting in episodic airflow obstruction. It is also one of the leading causes of morbidity in children and hospital admissions. Current treatments, although helpful, are still unable to prevent childhood asthma exacerbations completely. Objectives: To study the clinical profile and predisposing factors for acute severe asthma in children. Methods: This prospective study was conducted between January 2015 and December 2015 in a tertiary care teaching hospital. Children between the age group of 5 and 18 years admitted with symptoms and signs of acute severe asthma formed the study group. Detailed history and examination were recorded in a systematically designed pro forma, and these patients were evaluated for the predisposing factors. Results: Out of 100 children with acute severe asthma, the predominant age group was between 5 and 10 years (68%). Boys are more commonly affected than girls in the ratio of 1:1.2. The most common predisposing factors were family history of asthma (60%), atopy (32%), and dermatitis (23%). The common risk factors responsible for acute exacerbations were viral infections (83%), poor drug compliance (68%), and exposure to house dust (61%). 55% of the children had acute exacerbation during the winter season. The common comorbid conditions were rhinosinusitis (35%), obesity (23%), and gastroesophageal reflux (9%). Eosinophilia was seen in 62% of the children with acute severe asthma. Conclusion: In the present study, majority of the asthmatics were males and belonged to urban area. Viral infections were the predominant factor for exacerbations and others like family, and previous history of atopy/allergic rhinitis/dermatitis, food allergy, indoor and outdoor pollution, seasonal variations, and comorbid conditions like obesity and rhinosinusitis were the common predisposing risk factors.